EFFECT OF ANTIVIRAL THERAPY ON CARDIOHEMODYNAMIC INDICATORS IN PATIENTS WITH CHRONIC VIRAL HEPATITIS AND LIVER CIRRHOSIS - M. V. Chistyakova; A. V. Govorin; E. V. Radaeva (Столичная издательская компания, 2017)
Aim. To study the effect of antiviral therapy (AVT) on some cardiohemodynamics indicators in patients with chronic viral hepatitis (CVH) and viral liver cirrhosis (VLC).Material and methods. Doppler echocardiography, tissue Doppler echocardiography, 24-hour ECG monitoring, assessment of the blood flow in the portal vein and in the splenic artery were performed in patients with CVH (n=16) and VLC (n=16) initially and after the course of AVT with interferon and ribavirin leading to sustained virological response.Results. The improvement of systolic and diastolic function of the left ventricle (LV), decrease inLV myocardial mass (from 170 [225.5;213.5] to 159 [146;167] g; p<0.001), and size of the left atrium (LA; from 37 [34;40] to 35.5 [33;38] mm; p<0.001) were found in patients with CVH after AVT. Reduction in the autonomic nervous system tonus was also observed. Decrease in the blood flow rate in the splenic artery (from 107 [95;126.2] to 77 [67.2;99] cm/s; p<0.001) and in the portal vein (from 29 [20;31] to 19 [18;23] cm/s; p<0.001) were detected. Reduction inLV myocardial mass, LA size, systolic blood pressure in pulmonary artery (from 34 [29;38] to 30 [26;31] mm Hg; p<0.001), and the autonomic nervous system tonus were also observed after AVT in patients with VLC. The correlations between the maximum speed of the first negative peak (Em) in the mitral valve fibrous ring and increased viral load (r=0.31; p<0.05), as well as between the diameter of the portal vein and pulmonary artery pressure (r=0.77, p<0.05) were found.Conclusion. Results of the study suggest that patients received AVT have better cardiohemodynamic indicators than patients without specific treatment.